2018
DOI: 10.1155/2018/5470814
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Doped Nano Laponite Coating on Poly(butylene Succinate) Scaffold with Antibacterial Properties and Cytocompatibility for Biomedical Application

Abstract: An ideal artificial bone will likely be multifunctional, combining different technologies to simultaneously promote bone regeneration while inhibiting microbial infection. In this study, copper- (Cu-) doped nano laponite (cnLAP) was prepared by a cation-exchanged method, and the cnLAP coating on poly(butylene succinate) (PBSu) scaffold was fabricated by poly(dopamine) modification. The results showed that incorporation of Cu ions into nano laponite (nLAP) did not have obvious effects on the morphology and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The total releases of Si 4+ ions from the scaffolds during 21 days were similar and in the range of 152.82–153.89 ppm. Similarly, Tang et al 20 reported the releases of Si 4+ ions from the scaffolds coated with LAP and copper‐loaded LAP were similar.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The total releases of Si 4+ ions from the scaffolds during 21 days were similar and in the range of 152.82–153.89 ppm. Similarly, Tang et al 20 reported the releases of Si 4+ ions from the scaffolds coated with LAP and copper‐loaded LAP were similar.…”
Section: Resultsmentioning
confidence: 71%
“…To investigate the release of Si 4+ and Co 2+ ions from the scaffolds, samples (0.5 × 0.5 cm 2 ) were soaked in the culture medium in a 96‐well plate, the media was refreshed after 1, 3, 7, 10, 14, and 21 days and the concentrations of Si 4+ and Co 2+ ions released from the PCL@CMC/LAP and PCL@CMC/LAP‐Co scaffolds in the media were obtained by inductively coupled plasma atomic emission spectrometry (ICP‐OES; Varian 715‐ES, USA) 20 …”
Section: Methodsmentioning
confidence: 99%
“…In the case of an application in the medical field, biodegradable polyesters are usually processed in the shape of fibers to find application as scaffolds. Tang et al [ 300 ] coated PBS scaffolds, obtained using the salt leaching method, with copper-doped nano laponite (cnLAP). This material was to be applied in bone tissue engineering; therefore, the authors used nLAP to promote the osteogenic differentiation of human mesenchymal stem cells.…”
Section: Polyestersmentioning
confidence: 99%
“… Photographs of E. coli ( a – d ) and S. aureus ( e – h ) colonies’ growth after incubation for 24 h with PBS ( a , e ), nano laponite (nLAP)-coated PBS (nLBC) ( b , f ), and Cu–nLAP-coated PBS ( c , g ) scaffolds with vancomycin as a positive control ( d , h ). Reproduced from [ 300 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation